Performance of Prestressed Anchor Cables Supporting Deep Foundation Pit of a Subway Station during Spring Thaw - Chuntao Feng; Zhihe Cheng; Lei Zhu (Geofluids)
Based on the deep foundation pit for a subway station in Changchun (China), a 3D numerical model of water–heat coupling in a prestressed pile anchor system was established to determine its performance in freezing and thawing seasons in alpine areas. Its reliability was confirmed using field monitoring data on the prestressed anchor cables, which demonstrated changes in surface subsidence, anchor cable axial force, and pile horizontal displacement during spring thaw. The results demonstrated different degrees of elevation of the ground surface at the beginning of the spring thaw depending on whether the ground surface was at 2, 5, or 8 m from the pit excavation surface. Moreover, they demonstrated the occurrence of melting and surface subsidence when the temperature rises above 0°C, and that the axial force of the anchor cables fluctuates at the beginning of spring thaw but stabilizes in its middle and late stages. The phenomenon of pile horizontal displacement during the spring thaw could be roughly divided into three stages, with the second stage resulting in the most significant displacement. These results can provide certain reference for deep foundation pit projects in alpine areas.